Design and construction of a twenty-five horse-power gasoline traction-engine - Richardson, Emmit D.; Brant, Walter J. (My University, 1906)
Introduction: Object: To design and construct at the shops of the Kansas State Agricultural College, a gasoline traction engine that shall fulfill the following requirements; The engine shall have but one set of gearing to be used for forward and reverse motion, dispensing with speed changing gearing, together with its expensive first cost and maintenance, noise, low efficiency and weight. The gearing shall be on stiff shafts and rigid centers, having no radius rods nor stub gearing. All gears shall be of crucible cast steel, and shall be of ample size to stand rough usage and wear. Master or bull gears shall have roller bearings. Differential gears shall be of the spur gear type and shall be placed on a counter shaft. The bull gears shall be attached to the drive wheels by means of ample spring cushion links to take off sudden strains on the gearing and frame. The crank shaft shall be given as steady a torque as possible by using four quadruple opposed cylinders. These cylinders shall be large enough to give the crank shaft as great a torque as is given to the crank shaft of steam engine of the same nominal rating. The governor shall be constructed so that it can be set and regulated to run the engine under complete control at any speed from 50 R. P. M. to 220 R. P. M., as desired. The cylinders shall be horizontal and shall be located as low as possible in order that they may be covered with cooling water when water in the tank is low. The engine shall be easily reversed and shall be fitted with two friction clutches, one for the traction gearing and one for the belt pulley.
Citation: Richardson, Emmit D. and Brant, Walter J. Design and construction of a twenty-five horse-power gasoline traction-engine. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Mechanical Engineering; Gasoline Traction Engine; Theses